Building Globally-Ready SMEs Through Strengthening Compliance and Risk Management with Indonesia-Uzbekistan Collaboration in Caringin Subdistrict, Bogor Regency - Eka Patra; Dewi Taurusyanti; Mutiara Puspa Widyowati; Retno Martanti Endah Lestari; Hasbi Rizki Suardi; Boburbek Akmaljon Ugli Khakimov; Farrukh Ravshanjon Ugli Turdikulov (Rescollacom (Research Collaborations Community), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the global economy, but face complex challenges related to regulatory compliance and risk management. A community service program themed